PEREMPUAN DAN PILKADA LANGSUNG - Sofa Marwah (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2015)
Direct local election (Pilkada Langsung) that initially aimed as medium to motivate woman representation on political domain,however still didn’t reach its goal. Until December 2006, from 296 district, only 61 (20,6 percent) that participated by woman candidate.Several studies explain that there isn’t significant impact of sex with political vote (Austin Ranney, 1999). Woman’s obstacle to participate ascandidate in local direct election generally correlated with social, ideological, and psychological problems, also strong patriarchal culture. Inaddition, UU No. 32 year 2004 still obliged every candidate to apply through political party. Woman often excluded early on party’s internalmechanism because women have minor strategic role. Furthermore, women also being hindered by fund, resources, and network problems.